Developing a grid-connected DFIG strategy for the integration of wind power with harmonic current mitigation - Hacil Mahieddine; Laid Zarour; Louze Lamri; Nemmour Ahmed Lokmane (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The aim of this paper is to present a study of the efficiency of the electrical part of a wind generation system. Two back-to-back PWM voltage-fed inverters connected between the stator and the rotor are used to allow bidirectional power flow. The second inverter grid side, has a role of a power active filter, to eliminate the harmonic generated by the non linear load, in the same time gives an active and reactive power needed by the rotor of DFIG. The harmonics of switching frequency in the current stator, pose a major problem in the moment where commutations in the diode bridge, to solve this problem, we introduce a small-sized passive LC filter for the purpose of eliminating high-frequency shaft voltage and grid current from a DFIG driven by a voltage-source pulse width-modulation rotor inverter controlled with SVM. The control theory is discussed, and the controller implementation is described. Design criteria are also given. The results of simulation tests show excellent static and dynamic performances.